From uncrowned king to the sage of profound greatness: Confucius and the Analects in early medieval China - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2017)
This chapter explores the question of Confucius as a sage of “profound greatness” who embodies the fullness of Dao in his being (xuansheng 玄聖). It also discusses briefly the development of Lunyu learning in early medieval China. Xuanxue is often translated as “neo-Daoism”. The merit of this translation is that it points to a new hermeneutical engagement with tradition, with a sharp focus on the concept of Dao. The idea of Confucius as a sage of profound greatness, wonders, and mystery opens up a rich space for intellectual development. Whereas suwang may be of particular value to understanding the Confucius of history, xuansheng brings the sage into the present, into the thick of philosophical debate about the source, direction, and end of human existence. Different views on whether the sage experiences emotions can be found already in the Zhuangzi. The Zhuangzi argues that all phenomena ultimately rest on stillness and quiescence.